1979
DOI: 10.1159/000250595
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidization and Hemiploidization Induced by PUVA <i>in viv</i><i>o</i>

Abstract: To obtain additional information on the in vivo injury induced by PUVA treatment, primary cultures were initiated from biopsies of the uninvolved skin of 15 PUVA-treated psoriatic patients, and the cells generated were analysed for morphological and chromosomal modifications. Three biopsies were obtained from each patient, the first one before commencing PUVA therapy (control) and the other two during the course of therapy. It was found that PUVA treatment has diverse effects on the mitotic activity, mitotic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The large proportion of cells < 4C at 28 days may be due to endoreduplication leading to polyploid fibroblasts with a 4C content. In fact, polyploidization has been described after PUVA treatment (3). Alternatively, as suggested by the results after blocking DNA replication by hydroxyurea this DNA synthesis may represent unscheduled DNA synthesis due to repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The large proportion of cells < 4C at 28 days may be due to endoreduplication leading to polyploid fibroblasts with a 4C content. In fact, polyploidization has been described after PUVA treatment (3). Alternatively, as suggested by the results after blocking DNA replication by hydroxyurea this DNA synthesis may represent unscheduled DNA synthesis due to repair.…”
Section: Discussionmentioning
confidence: 99%
“…The planar structure of psoralens facilitates their intercalation between DNA base pairs and – after photocyclo‐addition reactions – their covalent binding to DNA upon photoexcitation. Therefore, in addition to oxidative damage psoralen photoactivation generates mono‐ and biadducts leading to DNA interstrand cross‐links with increased chromosome breakage and DNA fragmentation (2), poly‐ and hemiploidization (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While their report was mainly based on light microscopic examinations, we have studied the ultrastructural events. Examining the chromosomal alterations due to PUVA exposure, Omar et al ( 6 ) argue that multimicronucleate cells are formed by miotic division in G I phase of the cell cycle. At the ultrastructural level we found that multimicronucleate cells contain bizarre nuclear elements interconnected by heterochromatic extensions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note would also be that polykaryocytes may occur after PUVA (psoralen and ultraviolet A) therapy. 8 Although the patient was diagnosed with psoriasis vulgaris 15 years before the salivary gland biopsy, it is questionable whether an eventual PUVA treatment might have an impact on the present salivary gland lesions.…”
mentioning
confidence: 99%